Examining Educational Issues with 20 Private School Educators in Ecuador: Examinando problemas educativos con 20 educadores en una escuela privada en Ecuador (Papeles, 2022)
The Ecuadorian educational system has been transformed by the implementation of the National Ten-Year Plan (PDN, for its Spanish title, Plan Decenal Nacional), which was renewed until 2025. This qualitative study examined the self-reported perceptions of 20 private elementary school teachers regarding the Ecuadorian educational system. Study questions addressed (1) participants’ perceptions of the educational system using a survey based on the 5Essentials inquiry tool developed by Langley (2009) as an evaluative measure, and (2) challenges educators identified as barriers to learners’ academic achievement. Survey validity was evaluated by three Ecuadorian educators from the area where this research was conducted. Data collected from teachers were triangulated utilizing administrators’ interviews and an analysis of the school’s policies. Study findings suggest that participating teachers felt that they had received insufficient and limited support from school administration and parents, leading to teacher disempowerment.
Keywords: Academic support; teacher disempowerment; teachers’ self-esteem; educator’s role as leader; Ecuadorian context